2011
DOI: 10.1016/j.jallcom.2011.02.065
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation features of plastic deformed Zr-based bulk metallic glass

Abstract: a b s t r a c tThe surface morphology of in situ deformed, pre-deformed, undeformed and crystallized Zr 47.9 Ti 0.3 Ni 3.1 Cu 39.3 Al 9.4 bulk metallic glass in air at elevated temperatures are investigated to improve the understanding of the effect of plastic deformation on the oxidation. The plastic deformation is performed through instrumental macroindentation, while could provide a well developed shear offset pattern around the indents at lower temperatures. The oxidation experimental results show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Although some research works have discussed the multiplestage parabolic rate law and ionic diffusion phenomenon during BMG oxidation [13][14][15][16], few attentions have been paid to the relationship between crystallization and oxidation kinetics. Also, detailed investigations on the effects of thermal parameters on surface morphology evolution especially the segregation phenomena are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Although some research works have discussed the multiplestage parabolic rate law and ionic diffusion phenomenon during BMG oxidation [13][14][15][16], few attentions have been paid to the relationship between crystallization and oxidation kinetics. Also, detailed investigations on the effects of thermal parameters on surface morphology evolution especially the segregation phenomena are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…So far the oxidation behavior of Zr-based BMGs has not been investigated for the purpose of surface engineering, but rather to investigate the oxidation behavior. Several published investigations [17][18][19][20][21][22] reported the oxidation behavior of Zr-based BMGs over the temperature range of their super-cooled liquid region (ΔTx). Zhang et al [23] studied the oxidation behavior of the Zr55Cu30Al10Ni5 BMG in air within the temperature range 693-743 K for different durations.…”
mentioning
confidence: 99%
“…At elevated temperatures, Zr-based BMG exhibits strong accelerated corrosion in air with denser and larger particles forming on the surface, which become enriched with copper and oxygen (Zhang et al, 2014). Moreover, it was found that plastically deformed features are more prone to oxidation than undeformed areas (Hu et al, 2011). Figure 14 shows the compositional distribution across the height of the features after 600 molding cycles.…”
Section: Tool Lifementioning
confidence: 99%